Abortion and Rape Laws in Pakistan: A Sharī‘ah-Based Analysis - Qurratul-Ain-Munir-Minhas; Niazi, Samia Maqbool (Islamic Studies, 2020)
Rape is the most heinous act that can be committed against women and their families, often resulting in both short- and long-term complications. Abortion in the case of rape is an issue of social justice, human autonomy, and women’s health. Pakistani laws do not provide freedom for women to choose abortion for themselves in normal circumstances nor do they cover the issue of rape-related pregnancies. This article deals with the analysis, explanation, and discussion of rape and abortion. The issue of pregnancy as a consequence of rape has also been highlighted with reference to abortion laws. Moreover, the legal rights and shelters offered to victims and their children have been critically examined. The article looks at the rulings on rape and abortion in both classical Islamic law and Pakistan’s legal system, highlighting basic, substantive, and procedural gaps in the legal framework.